(untitled) (Balneo and PRM Research Journal, 2021)
We have lived in an era in sports history in which due to the intensity of the confrontations between athletes, disorders manifested by headaches, shoulder, pelvis and knee aches etc. appear more often. The performers during puberty require special attention on their morpho – functional development from the kynesiotherapist who is part of the multidisciplinary team, due to many transformations of the human body specific at this age category. 13 juniors female athletes have participated to the study, being assessed anthropometric, plantar pressures and posture with softwear FreeStep by Sensor Medica, biomechanical analysis and from technical & tactical point of view by 5 tests with DartFish 360S. Within the statistical – mathematical analysis, we have used Pearson correlation coefficient which favoured the identification of the strongest correlations resulted from the technical – tactical - anthropometric – plantar pressures and postural unbalances (r > 1.00 at test 1 and r > 0.84 at test 2). Assumption: It is assumed that by using established methods and means to assess postural deficiencies and to assess the level of consolidation of the topspin attack, we can identify the correlations between them which would facilitate the creation in the future of an efficient postural improvement program. The goal is to improve the quality of life and sports performance in junior female table tennis players. The conclusions of this study demonstrate the fact that the mobility of the spine in frontal plan, high thoracic elasticity and an increased lateral mobility on the opposite side of the active arm represent advantages intended to optimize the attack by topspin, while the supraponderability, the pain in lumber area and the shoulder’s asymmetry constitute disruptive factors of attack’s performance.